مساهمة قطاع التعليم العالي في تحقيق تحديات التنمية البشرية في الجزائر دراسة قياسية خلال الفترة 1990-2017 باستخدام نموذج Vecm - دقيش, جمال; اولاد ابراهيم, ليلى (جامعة الوادي - University of Eloued, 2021)
يهدف هذا العمل إلى تبيان دور الاستثمار في رأس المال البشري مقاسا بمخرجات التعليم العالي (خريجي الجامعات، الطلبة المسجلون، عدد الأساتذة وميزانية التعليم العالي) على مقومات تحقيق التنمية البشرية والتي تمثل جزء من عملية التنمية الاقتصادية والاجتماعية كمتغير تابع (تضم ثلاث مؤشرات فرعية تتمثل في متوسط العمر المتوقع والتعليم ومستويات المعيشة). وذلك بإجراء دراسة قياسية لتبيان أثر مخرجات التعليم العالي على مؤشرات التنمية البشرية بالاعتماد على نموذج شعاع متجه تصحيح الخطأ، من خلال الاستعانة بمعطيات إحصائية تتعلق بالاقتصاد الجزائري خلال الفترة 1990-2017. توصلت النتائج إلى أن تكوين الموارد البشرية يعتبر المحدد الأساسي للتنمية البشرية في الجزائر من خلال التركيز على الكفاءات واليد العاملة المؤهلة بما يتناسب واحتياجات سوق العمل. بالإضافة الى غياب علاقة توازنية في الاجل الطويل مما يدل على أن قطاع التعليم العالي لا يزال بعيد المنال في تحقيق اهداف التنمية البشرية كونه أصبح يرتكز على الكم دون الجودة. This work aims to demonstrate the role of investment in human capital as measured by the outcomes of higher education (university graduates, registered students, number of professors and the budget of higher education) on the components of human development, which are part of the process of economic and social development as a dependent variable (comprising three subindicators of life expectancy, education and living standards). By conducting a standard study to show the impact of higher education outcomes on human development indicators based on the model of a beam vector higher education outcomes on human development indicators based on the model of a beam vector to correct the error, using statistical data related to the Algerian economy during the period 1990-7102 The results concluded that the formation of human resources is the main determinant of human development in Algeria by focusing on qualified and qualified workforce in proportion to the needs of the labor market. In addition to the absence of a balanced relationship in the long term, which indicates that the higher education sector is still a distant goal in achieving the human development goals, as it has become based on quantity without quality.
The contribution of the higher education sector to achieving the challenges of human development in Algeria – An empirical study during 1990-2017 using VECM
مقال
Keywords: التعليم العالي ; التنمية البشرية ; نموذج شعاع متجه تصحيح الخطأ ; اليد العاملة المؤهلة